Chitosan nanoparticles as therapeutic protein nanocarriers: The effect of ph on particle formation and encapsulation efficiency. Issue 9 (8th January 2013) - Mattu, Clara; Li, Ruo; Ciardelli, Gianluca
<x xml:space="preserve">Abstract</x> In the past, tripolyphosphate (TPP)‐crosslinked chitosan (CS) nanoparticles (CSNPs) have been widely applied for the delivery of biomacromolecules, because of their mild preparation conditions. However, poor uniformity and burst release limit their application to some extent. In this study, we investigated the effect of pH on the formation and on protein encapsulation efficiency (EE) of CSNPs. Results revealed that smaller particles are formed at lower pH and that the size distribution is conjointly influenced by pH and CS/TPP mass ratio. EE of bovine serum albumin (BSA) increased significantly with pH value. The influence of the pH of the crosslinker (TPP) solution was also studied, showing that CSNPs prepared with basic TPP solution (pH 9.5) had larger size, higher yield, and BSA EE compared with those obtained with acidic TPP solution (pH 5.5). Characterization by Fourier transform infrared‐attenuated total Reflectance (FTIR‐ATR) spectroscopy and SEM as well as the in vitro BSA release analysis revealed that the pH of the TPP solution might influence CSNPs' properties, by changing the conformation of polymer chains. This study analyzes the formation of CSNPs and protein encapsulation mechanisms at different pH values of both the polymer and the crosslinker solutions, suggesting strategies to overcome some of the major drawbacks of CSNPs as protein nanocarriers for therapeutic applications. POLYM. COMPOS., 34:1538–1545, 2013. © 2013 Society of Plastics Engineers